Attitudes of nurses from a public teaching hospital regarding the nursing process - Almeida, Beatriz Pera de; Dias, Flávia de Souza Barbosa; Cantú, Priscila Miranda; Duran, Erika Christiane Marocco; Carmona, Elenice Valentim (Revista da Escola de Enfermagem da USP, 2019)
Objective To measure the attitudes of nurses on nursing process at a public teaching hospital. Method A cross-sectional and analytical study conducted with nurses at a tertiary hospital. It was applied an instrument to characterize sample, as well as the Positions on the Nursing Process instrument, which measures nurses’ attitudes in relation to the nursing process. There are 20 items to be considered, in which the minimum possible value is 20 and the maximum of 140. The data were submitted to descriptive statistics and the variables of interest were analyzed by the Mann-Whitney, Student’s t-test, Chi-square test, Kruskal-Wallis, Spearman’s correlation coefficient and hierarchical multiple regression models, as appropriate. Results In a sample of 226 nurses, 80.5% (182) stated that they performed pdaily. The mean score of the instrument was 102.50 (SD = 21.76). The item “routine/creative” had a lower score (3.54), while “unimportant/important” had a higher score (5.81). Conclusion The nurses reported being in favor and presented positive attitudes about nursing process, in addition to considering it important, but routine, as well as affirming little or no contact with research, classes or events on the subject.